EVALUASI PENGENDALIAN INTERNAL UNTUK MEMINIMALISASI RISIKO TERJADINYA KECURANGAN PADA SIKLUS PENDAPATAN DAN SIKLUS PENGELUARAN UD.X DI SURABAYA - Natalie Falen Utomo; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to analyze and evaluate the internal control system on the revenue and expenditure cycle to find some weaknesses that often occurred on X company. A qualitative approach is used with a business that runs in reparation and selling spare part on Surabaya as its object. The process of internal control evaluation of this research are based on COSO Framework principles. Benefits of this research are applied research, because this research applied science to some of practical issues to evaluate problems which will be handled and provide recommendations to that issues. The result explains that there are some weaknesses that often occur on X company, which will incur significant losses if it happens continuously. Therefore, this research is intended to provide solutions or recommendations to X company, so it can improve efficiency of X company’s operational.